2006
DOI: 10.1016/j.ejheart.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cytokines and tumour markers in patients with chronic heart failure

Abstract: Aims: Serum levels of some cytokines and tumour markers are elevated in patients with chronic heart failure (HF). We aimed to investigate the relationship between circulating levels of cytokines and tumour markers in patients with HF. Methods: We included 35 HF patients and 33 normal controls. HF patients were divided into two groups: mild HF (NYHA class I/II) (n = 10) and severe HF (NYHA class III/IV) (n = 25). Serum cytokine levels (TNF-a, IL-1 h, IL-6, and IL-10) were measured by ELISA and tumour markers (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 35 publications
(70 reference statements)
2
73
0
Order By: Relevance
“…(56,57) Moreover, patients who have metabolic diseases such as diabetes and chronic cardiac disease also show high TNF-a levels in the blood serum. (58)(59)(60) Although the TNF-a level itself in this animal study might not be able to extrapolate to the human subject, bone formation and osteogenesis would be decreased in such patients because of the continuously high TNF-a level. In the future, targeting of TNF-a inhibition might be a useful therapeutic strategy to accelerate bone formation/osteogenesis in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…(56,57) Moreover, patients who have metabolic diseases such as diabetes and chronic cardiac disease also show high TNF-a levels in the blood serum. (58)(59)(60) Although the TNF-a level itself in this animal study might not be able to extrapolate to the human subject, bone formation and osteogenesis would be decreased in such patients because of the continuously high TNF-a level. In the future, targeting of TNF-a inhibition might be a useful therapeutic strategy to accelerate bone formation/osteogenesis in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kosar [16] demonstrated that high CA125 levels in HF patients were correlated with inflammatory cytokines levels, suggesting a relationship between CA125 and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that mesothelial cells can secrete CA125 in response to activation of cytokines. Thus, the activation of either TNFalpha or interleukin-6 has been associated with elevated CA125, and the increase of these cytokines correlates with the severity of HF [7,18] . It has been suggested that increased CA125 can be a sign of both congestion and inflammation; both parameters have been associated with poor prognosis in HF patients.…”
Section: Ca125 and Hfmentioning
confidence: 99%
“…It is a highmolecular-weight glycoprotein synthesized by epithelial cells of the serosa when there is inflammation and increased interstitial fluid; therefore, its level is elevated in the presence of pleural or pericardial effusion and ascites. Elevated CA125 has also been found in patients with HF, with or without fluid retention [16][17][18][19] . Although its release mechanisms are not yet well understood, they correlate with increased left ventricular end-diastolic pressure, higher BNP level, and worse New York Heart Association (NYHA) functional class [20,21] .…”
Section: Introductionmentioning
confidence: 99%